âSay a Little but Say It Wellâ: Assessing the Impact of Social Media Communication on Value Co-creation, Online Customer Experience, and Customer Well-Being - Awan, M.I. (Frontiers Media S.A., 2022)
The purpose of the study is to identify how both tourism service provider- and tourist-generated social media communication affect the value co-creation process and how this can affect online customer experience and customer wellbeing. A questionnaire survey was used and 361 valid responses were obtained from Malaysian citizens. The research findings showed that tourism service provider- and tourist- generated social media communication positively influence value co-creation. Similarly, value co-creation positively influences cognitive and affective experiential states and these two states positively influence customer wellbeing. Furthermore, value co-creation partially mediates the relationship between social media communication and online customer experience, whereas, online customer experiences also partially mediate the relationship between value co-creation and customer wellbeing. This study has tried to establish theoretical relationship between some significant variables and the findings would aid both academicians and practitioners in formulating strategies for future. Copyright Â© 2022 Awan, Shamim and Saleem.